FAKTOR-FAKTOR YANG MEMPENGARUHI KOMPLIKASI PADA PASIEN DIABETES MELLITUS DI PUSKESMAS DANDER KABUPATEN BOJONEGORO TAHUN 2018 - Sri Mulyani, Sri Mulyani; Dwi Agung Susanti, Dwi Agung Susanti; Ratna T, Ratna T (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2019)
Most of the Diabetics Mellitus patients who come to the Public Health Center treatment have been complicated. These complications occur because, non-compliance of patients to the Diabetics Mellitus diet, not routine health control for lazy queuing, and ignorance of patients if you should consume drugs regularly. The aim of this research is to know the factors that influence the complication in diabetics mellitus patient at Dander Health Center of Bojonegoro Regency. Descriptive research design with a population of 78 respondents with a sample of 26 respondents, sampling using the technique of non-probability sampling that is by way of Purposive Sampling. Data collection using questionnaires and observation sheets and then performed data processing by editing, codings, coring, tabulating, and presented in tabular form. The results of this study indicate that the majority of respondents are not independent in their blood glucose monitoring, more than half of respondents are not complience in the diet of diabetics mellitus, most respondents are not regular in physical activity and compliance in taking medication, some respondents do not routinely control the treatment, and less than some respondents with obesity weight so it can affect complications in Diabetics Mellitus patients.